Intelligence a very short introduction - Deary, Ian J. (Very short introductions, 2020)
Some people appear to be smarter than others, but how do we measure intelligence? Why do some people have better thinking powers than others? What does intelligence predict about people's health and social outcomes? This "Very Short Introduction" uses the best, large-scale psychological data to answer important questions about intelligence, such as how environment, genes, brain structure, gender, and age affect people's thinking skills. It asks whether intelligence increased over the 20th century. Ian Deary also considers the new field of cognitive epidemiology, which discovers links between higher intelligence and better health, lower rates of illness, and longer life. --